King Cobra and snakebite envenomation: on the natural history, human-snake relationship and medical importance of Ophiophagus hannah - Tan,Choo Hock (2021)
Abstract King Cobra (Ophiophagus hannah) has a significant place in many cultures, and is a medically important venomous snake in the world. Envenomation by this snake is highly lethal, manifested mainly by neurotoxicity and local tissue damage. King Cobra may be part of a larger species complex, and is widely distributed across Southeast Asia, southern China, northern and eastern regions as well as the Western Ghats of India, indicating potential geographical variation in venom composition. There is, however, only one species-specific King Cobra antivenom available worldwide that is produced in Thailand, using venom from the snake of Thai origin. Issues relating to the management of King Cobra envenomation (e.g., variation in the composition and toxicity of the venom, limited availability and efficacy of antivenom), and challenges faced in the research of venom (in particular proteomics), are rarely addressed. This article reviews the natural history and sociocultural importance of King Cobra, cases of snakebite envenomation caused by this species, current practice of management (preclinical and clinical), and major toxinological studies of the venom with a focus on venom proteomics, toxicity and neutralization. Unfortunately, epidemiological data of King Cobra bite is scarce, and venom proteomes reported in various studies revealed marked discrepancies in details. Challenges, such as inconsistency in snake venom sampling, varying methodology of proteomic analysis, lack of mechanistic and antivenomic studies, and controversy surrounding antivenom use in treating King Cobra envenomation are herein discussed. Future directions are proposed, including the effort to establish a standard, comprehensive Pan-Asian proteomic database of King Cobra venom, from which the venom variation can be determined. Research should be undertaken to characterize the toxin antigenicity, and to develop an antivenom with improved efficacy and wider geographical utility. The endeavors are aligned with the WHO´s roadmap that aims to reduce the disease burden of snakebite by 50% before 2030.